(untitled) (Revista Peruana de Investigación Educativa, 2021)
Based on a portrait of the situation of education in the initial years of the history of independent Peru, the article traces the policy deployed by the State regarding the organization of schools and the establishment of contents of what students were taught in elementary or basic levels and intermediate or secondary levels. For this we focus on an analysis of the most used texts in the schools of Peru between 1821-1850. We conclude that the State put little effort into regulating the materials used in the schools, so that the texts used in them were, mainly, at the initiative of educators who ran private schools in Lima or other important cities. The content of these texts did not reflect the ideals of independence and of the republic as a form of government and social coexistence, but essentially inherited the approaches that had been used in the viceregal era.